Methanosarcina acetivorans: A Model for Mechanistic Understanding of Aceticlastic and Reverse Methanogenesis - Ferry, James G. (Frontiers in Microbiology, 2020)
Acetate-utilizing methanogens are responsible for approximately two-thirds of the one-billion metric tons of methane produced annually in Earth’s anaerobic environments. Methanosarcina acetivorans has emerged as a model organism for the mechanistic understanding of aceticlastic methanogenesis and reverse methanogenesis applicable to understanding the methane and carbon cycles in Nature. It has the largest genome of microbes in the domain Archaea, supporting a metabolic complexity that enables a remarkable ability for adapting to environmental opportunities and challenges. Biochemical investigations have revealed an aceticlastic pathway capable of fermentative and respiratory energy conservation that explains how M. acetivorans is able to grow and compete in the environment. The mechanism of respiratory energy conservation also plays a role in overcoming endothermic reactions in M. acetivorans that are key to reversing methanogenesis.